TRAINING MODEL OF EVASION TECHNIQUES IN DOUBLE ART CATEGORY OF PENCAK SILAT BASED ON ATTACK MACHINE - Bhakti, Muhammad Wiyata; Johansyah Lubis; Sri Nuraini (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Pencak silat, as a traditional martial art, has evolved into a modern combat sport that is now featured in various national and even international events. This research has developed 11 training models for evasion techniques in the double category of pencak silat using the Attack Machine and an Instrument Test to measure the speed of evasion techniques, named the Attack Machine Test. This research was conducted using the Research and Development method. The research procedure followed the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. Data collection involved 30 active students specializing in the art category, particularly doubles, using testing and measurement techniques as the Instrument Test for collecting pretest and posttest data (Attack Machine Test). The data analysis presented includes descriptive quantitative analysis and qualitative analysis. The results of this study show that the average pretest score was 58.3 and the posttest score was 67.5, with standard deviations of 21.104 and 17.555, respectively. In the t-test table for Equality of Means, with a significance level of < 0.05 for the One-Sided p Mean Difference Two-Sided p Std. Error Difference, it indicates the significant improvement in training effectiveness and reaction speed in the double category.